Optimal irrigation water salinity enhances tomato(Solanum lycopersicum L.) yield in sand culture by regulating substrate salinity - Wenge Jiang; Zhi Gong; Yuhui Yang; Zhanming Tan; Zhaoyang Li; Dongwei Li (Agricultural Water Management)
Effectively utilizing saline water and yellow sand resources is crucial for addressing Xinjiang's two significant agricultural challenges: freshwater scarcity and soil salinization. Integrating water conservation and salt management in this region requires innovative irrigation strategies. In this study, we conducted a controlled greenhouse experiment using tomato plants (Solanum lycopersicum L.) grown in yellow sand, with six irrigation treatments: a groundwater control (CK, salinity 0.80–1 g/L) and five saline water salinity gradients (2–6 g/L). We systematically investigated the effects of different irrigation salinities on the growth and yield of sand-cultured tomatoes. Over two growing seasons, saline water irrigation led to increased substrate water content and salinity. An irrigation salinity of 3 g/L proved optimal, significantly improving root development (root length density increased by 23.21 %; mean root diameter by 26.71 %), which resulted in a 9.76 % increase in dry matter accumulation and a 35.24 % yield improvement compared to the control. In contrast, higher salinity levels (≥4 g/L) inhibited root growth and reduced yield by 34.02 %. Both TOPSIS entropy weighting and principal component analysis identified 3 g/L as the optimal salinity for tomato cultivation. Structural equation modeling (SEM) further revealed that optimal irrigation water salinity enhances tomato yield in sand culture by regulating substrate salinity to promote plant growth, offering a novel theoretical framework for water-land resource sustainable management in arid regions.